Volume 2: Combustion, Fuels and Emissions 2009
DOI: 10.1115/gt2009-59263
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between the Acoustic Pressure Fluctuations and the Unsteady Flow Field Through Circular Holes

Abstract: Gas turbine combustion systems are prone to thermo-acoustic instabilities, and this is particularly the case for new, low emission, lean burn type systems. The presence of such instabilities is basically a function of the unsteady heat release within the system (i.e. both magnitude and phase), and the amount of damping. This paper is concerned with this latter process and the potential damping provided by perforated liners and other circular apertures found within gas turbine combustion systems. In particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A semi-infinitely long cylindrical vortex sheet with the same radius as the hole was assumed to be shed from the hole edge. Howe's model can be slightly modified by adding a small mass inertial term to account for a small hole length; this approach has been widely used to predict the acoustic response of very short holes over recent years [1,2,[12][13][14][15][16]. Another approach which does not explicitly consider the shed vorticity was proposed by Bellucci et al [3].…”
Section: Introductionmentioning
confidence: 99%
“…A semi-infinitely long cylindrical vortex sheet with the same radius as the hole was assumed to be shed from the hole edge. Howe's model can be slightly modified by adding a small mass inertial term to account for a small hole length; this approach has been widely used to predict the acoustic response of very short holes over recent years [1,2,[12][13][14][15][16]. Another approach which does not explicitly consider the shed vorticity was proposed by Bellucci et al [3].…”
Section: Introductionmentioning
confidence: 99%
“…This parameter is used with different normalization factors for an assessment of the efficiency of liners (e.g., [33,34]) and Helmholtz resonators (e.g., [6,13,14]). Here, it is employed normalized with the squared pressure amplitude:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…32 was the acoustic response of a simple round orifice (with throughflow) to an incident acoustic wave. This problem had previously been studied experimentally by Rupp et al (50) ; the experimental set-up used is indicated in Fig. 28.…”
Section: Aeroacousticsmentioning
confidence: 99%
“…The two components of impedance -resistance (R) and reactance (X) -are used to characterise (R) the dissipative Figure 28. URANS CFD predictions of acoustically excited orifi ce fl ow (32,50) . Figure 29.…”
Section: Aeroacousticsmentioning
confidence: 99%